2011
DOI: 10.1093/jxb/err280
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase AtrbohD and AtrbohF function in ROS-dependent regulation of Na+/K+ homeostasis in Arabidopsis under salt stress

Abstract: Maintaining cellular Na(+)/K(+) homeostasis is pivotal for plant survival in saline environments. However, knowledge about the molecular regulatory mechanisms of Na(+)/K(+) homeostasis in plants under salt stress is largely lacking. In this report, the Arabidopsis double mutants atrbohD1/F1 and atrbohD2/F2, in which the AtrbohD and AtrbohF genes are disrupted and generation of reactive oxygen species (ROS) is pronouncedly inhibited, were found to be much more sensitive to NaCl treatments than wild-type (WT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
270
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(280 citation statements)
references
References 44 publications
6
270
0
4
Order By: Relevance
“…Recently, it has been demonstrated that ROS production by NADPH oxidases is crucial for mediating salt stress tolerance and that exogenous H 2 O 2 improves salinity tolerance in Arabidopsis (Ma et al, 2012). During the initial phase of salt stress, increased ROS levels might act as an acclimation signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that ROS production by NADPH oxidases is crucial for mediating salt stress tolerance and that exogenous H 2 O 2 improves salinity tolerance in Arabidopsis (Ma et al, 2012). During the initial phase of salt stress, increased ROS levels might act as an acclimation signal.…”
Section: Discussionmentioning
confidence: 99%
“…Salt-induced ROS are predominantly represented by H 2 O 2 , both outside and inside the cell Pang and Wang, 2008). Extracellular ROS production depends on the activity of NADPH oxidases that contribute to salt stress tolerance in Arabidopsis thaliana (Ma et al, 2012). In rice (Oryza sativa), NADPH oxidase-dependent H 2 O 2 production emerges within several minutes of salt stress (Hong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the kinase interacts with AtrbohF in bimolecular fluorescence complementation assay, suggesting that NADPH oxidase could be a SnRK2.6/OST1 substrate in vivo (Sirichandra et al, 2009). AtrbohF and AtrbohD (another NADPH oxidase), which are abundant in plant roots, are involved in ROS production in response to several abiotic and biotic stresses (Sagi and Fluhr, 2006;Suzuki et al, 2011;Ma et al, 2012;Marino et al, 2012). It was shown that phosphorylation and Ca 2+ binding are needed for AtrbohD and AtrbohF activation (Ogasawara et al, 2008;Kimura et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the mean protein proximity value increased to 0.42 6 0.09 (P < 0.01) and 0.35 6 0.04 (P < 0.05) (n = 10 cells) after ionomycin and calyculin A treatments, respectively, indicating that both Ca 2+ and phosphorylation enhanced mCherry-RbohD and GFP-Flot1 colocalization. RbohD plays a key role in the response to salt stress, and salt acclimation requires the ROS generated by RbohD (Xie et al, 2011;Ma et al, 2012). Therefore, we used FM4-64 to investigate the dynamics and endocytic pathways of GFP-RbohD under salt stress.…”
Section: Membrane Microdomains Contribute To the Localization And Intmentioning
confidence: 99%